Strike Action and the Academic Performance of Students of Alvan Ikoku Federal College of Eduction Owerri - Nkechi Nancy Abaekwume; Kenneth Agundu; Emmanuel Agoha; Annabel Uchechukwu Obinna-Akakuru (International Journal of Education, Teaching, and Social Sciences, 2022)
This study examined the influence of strike action on the academic performance of students in tertiary institutions with particular reference to Alvan Ikoku Federal College of Education, Owerri, Imo State. The population of the study was 635 academic staff in five schools of the college. A sample of 128 representing 20% of the population was taken. The study adopted a descriptive survey design while the instrument for data collection was structured questionnaire. The likertfour-point, scale rating was adopted whereas the data collected were analyzed using mean. The result of the data analyzed showed that strike action highly influences the academic performance of students in tertiary institution. Poor remuneration, negligence by government, conducive academic environment among others were identified as major causes of strike action. The researchers recommend that autonomy of tertiary institutions, adequate funding, and the re-orientation of staff to find alternative ways of expressing their grievances as measures to curb incessant strike actions in our tertiary institutions.